Lipid Production of Nanochloropsys under Environmental Stress - Moh. Muhaemin (Faculty of Mathtmatics and Natural Sciences, 2011)
The effect of environmental condition on lipid production of marine microalgae Nanochloropsys were observed. Basicy, the amount of total lipids depend on the NaCl and nitrogen concentration on culture medium. The total lipid highest yield (31.45%) was obtained in cell grown at 20% NaCl and 3.0 mM N. And the lowest yield (7.23%) obtained in cell grown at 10% NaCl and 6.0 mM N. The result showed that Nanochloropsys containing high amount of total lipid, and suggested to be used as suplemental ingredient for food to exceed the body performance.